The system of local self-government under government of A. V. Kolchak (The Case of Perm province) - V. I. Teterin (Омский научный вестник: Серия "Общество. История. Современность")
The article examines the problems of the development of the system of local selfgovernment bodies during the establishment of power by A. V. Kolchak in the Perm province. The great interest of scientists in the history of the Civil War made it possible to single out many problems that were not considered in Russian and foreign historiography. It is important to study the activities of the zemstvo and city government in new conditions. This became the goal of this study. During the revolution, the system of local self-government was subjected to significant changes, was actively involved in the political life of the country. However, in 1919, under A. V. Kolchak no longer played a big role in the political life of the zemstvo. In the Perm province, self-government was supposed to work in a frontline situation. With this in mind, the direction of development was only indicated, but in the summer of 1919, with the arrival of the Bolsheviks, the zemstvo was finally liquidated.